Morphological characterization and identification of endophytic fungi isolated from the leaf of Serpentina (andrographis paniculata Nees) collected from Motiong, Samar - Beduya, Napoleon Marrion P.; Fuentes, Rolly G. (2025)
Endophytic fungi are symbiotic microorganisms that form relationships with plants without causing disease. They are ubiquitous to slightly parasitic microorganisms that are part of the life-cycle of the plant. Fungal endophytes are diverse and are today being recognized for their potential chemical synthesizing abilities inside their hosts for secondary metabolites. This study utilized the medicinal plant Serpentina, Andrographis paniculata N. for the investigation of leaf fungal endophytes. Segments of exposed leaf tissue were seeded and placed in Potato Dextrose Agar in order to cultivate fungal endophytes after surface sterilization. There were twenty (20) pure culture isolates that were cultivated after 2 weeks of incubation under dark conditions to encourage growth of sexual structures and spores. There were 5 genera found to be present in the Andrographis paniculata, namely: Colletotrichum sp., Cylindrocarpon sp., Fusarium sp., Scytalidium sp., and Trichoderma sp.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.